2023
DOI: 10.21203/rs.3.rs-3116341/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The costs and benefits of clean cooking policies in low- and middle-income countries under real-world conditions

Marc Jeuland,
Ipsita Das,
Selena Galeos
et al.

Abstract: Clean cooking technologies have the potential to deliver tremendous health, environmental, climate, and gender equity benefits. We use the BAR-HAP model to analyze the regional and global costs and benefits of policies to support household-level transitions to cleaner technologies. The analysis provides realistic, evidence-based estimates of the impacts of policy interventions, while remaining conservative about factors such as stove usage rates, subsidy leakage rates, and exposure levels. These conservative a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Some research has suggested that strategies such as soaking beans or using energy efficient pots can reduce cooking times, but there is no evidence on the specific quantity of fuel savings that such behaviors could achieve ( Munthali et al, 2022 ; Nabukwangwa et al, 2023 ). Enhancing affordability and use of clean fuels through energy conservation measures would not only benefit households through time savings and potential economic and health impacts ( Jeuland et al, 2023 ), but would also contribute to reducing negative environmental impacts of biomass use, such as deforestation and climate change ( Goldemberg et al, 2018 ). A recent modeling analysis found that full transitions to LPG and/or electricity for cooking in 77 LMICs would nearly eliminate annual emissions of fine particulate matter (PM 2.5 ) and carbon monoxide (CO), significantly reduce well-mixed greenhouse gas emissions, and nearly eliminate emissions of the strongest short-lived climate forcing pollutants compared to a business-as-usual scenario ( Floess et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some research has suggested that strategies such as soaking beans or using energy efficient pots can reduce cooking times, but there is no evidence on the specific quantity of fuel savings that such behaviors could achieve ( Munthali et al, 2022 ; Nabukwangwa et al, 2023 ). Enhancing affordability and use of clean fuels through energy conservation measures would not only benefit households through time savings and potential economic and health impacts ( Jeuland et al, 2023 ), but would also contribute to reducing negative environmental impacts of biomass use, such as deforestation and climate change ( Goldemberg et al, 2018 ). A recent modeling analysis found that full transitions to LPG and/or electricity for cooking in 77 LMICs would nearly eliminate annual emissions of fine particulate matter (PM 2.5 ) and carbon monoxide (CO), significantly reduce well-mixed greenhouse gas emissions, and nearly eliminate emissions of the strongest short-lived climate forcing pollutants compared to a business-as-usual scenario ( Floess et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%